Principles and methods for automatic scaling of high‑load systems - Buhrov , Anatolii; Terenchuk , Svitlana (Ways to Improve Construction Efficiency, 2023)
This paper investigates a wide spectrum of use cases and the main approaches applied to Internet‑traffic processing by industry giants such as Netflix, YouTube, Disney+, TikTok, Facebook, Xbox Live, PlayStation Downloads, and Amazon Prime. It has been demonstrated that the defining characteristic of high-load systems is the need for automated resource management to process large volumes of real-time requests while ensuring high availability, reliability and stability amid dynamically changing workloads. The impact of key performance metrics on other functional characteristics has been analyzed. Based on these analyze, the system's key metrics set that guarantees system’s responsiveness under unpredictable conditions has been systematized and structured. Findings has indicated that system throughput depends on adaptive load balancing, whereas scalability determines the system’s capacity to adapt. Thus, efficient resource management and adaptive scaling algorithms makes it possible to reduce costs without losing performance. It has also been shown that the efficiency and resilience of high-load systems significantly depend on architectural solutions. Moreover, vertical scaling of the system enables increased performance of individual system nodes, while horizontal scaling provides better fault tolerance. It has been established that the main challenge in achieving economic efficiency lies in balancing scalability, performance and fault tolerance, while combined scaling strategies can help align these objectives. The relevance of developing models and methods for optimizing load adjustments timing has been highlighted, and directions for further research are outlined. The results these investigation may be used in the future to develop adaptive models and management methods of high‑load distributed systems resources that are able to operate effectively under conditions of dynamic unpredictable loads and increasing performance requirements..